Traditional Festivals in Southeast Asia: Unity in Diversity - Minh Tri Nguyen (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2025)
Traditional Southeast Asian festivals serve as vibrant expressions of cultural identity, reflecting historical continuity and regional diversity. Rooted in indigenous traditions and influenced by external cultural exchanges, these festivals embody the concept of "unity in diversity." This study explores the shared characteristics and distinct variations of traditional festivals across Southeast Asian nations, emphasising their roles in fostering social cohesion, reinforcing national identities, and preserving cultural heritage. Utilising a secondary research methodology, the study systematically examines documentary sources to identify thematic patterns across agricultural, religious, and New Year's festivals. The findings reveal that while the festivals exhibit diverse forms and rituals, they share common foundations in wet-rice agriculture, spiritual beliefs, and seasonal cycles. These festivals function as cultural markers and dynamic platforms for adaptation and modernisation in an increasingly globalised world. The study highlights the significance of these celebrations in sustaining regional cultural heritage while fostering cross-cultural appreciation among Southeast Asian nations.